Selection de Stylosanthes resistants a l'anthracnose: Rapport preliminaire - Mohamed-Saleem, M.A.; Adeoti, A.A. (1989)
Evaluates the susceptibility of stylo to anthracnose on 17 Stylosanthes guianensis lines acquired from CIAT and on two reference materials Cook and Verano stylo. Describes the two experiment sites-Kaduna and Kacchia. Presents data on disease score and fungal types isolated from samples of screened stylo lines and dry-matter & herbage crude protein of 19 stylo accessions.